The Shadow Puppet Theatre of Malaysia: A Study of Wayang Kulit with Performance Scripts and Puppet Designs by Beth Osnes. Jefferson, North Carolina: McFarland & Company, 2010 - Kevin Brown (Kajian Malaysia, 2012)
The Shadow Puppet Theatre of Malaysia: A Study of Wayang Kulit with Performance Scripts and Puppet Designs is the culmination of over 20 years of work by writer and theatre Professor Beth Osnes. She first traveled to Malaysia as a graduate student in search of a topic for her doctoral dissertation at the University of Colorado during the summer of 1989. What she found was an art form that was inspirational and beautiful, grounded in a culture that was equally so. In contrast to the more well-known Javanese style of wayang kulit, the Malaysian form is a bit more rough and more vital. Osnes explains: "Prepare yourselves for a bumpier ride complete with dips into raucous humor and ascents to moments of sublime beauty" (p. 7).